2018
DOI: 10.21071/edmetic.v7i2.10950
|View full text |Cite
|
Sign up to set email alerts
|

Percepción de habilidades docentes a través de las emociones mediante el uso de videojuegos de temática social

Abstract: La consideración del juego como herramienta educativa es una constante en la cultura humana. Actualmente, la esencia del juego es la misma, pero han cambiado los formatos para llevarlo a cabo. En éste marco nacen los videojuegos, los cuáles han tenido una vertiginosa evolución considerándose en los últimos años como elementos educativos mediante el Digital Game Based Learning. También se han tenido en cuenta las emociones como elementos propios de los procesos de aprendizaje vinculados con una serie de atribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
3
0
2
Order By: Relevance
“…It is significant that while some research studies report on the great use of digital tools [11]-mainly Augmented Reality [4,19,20], gamification [1][2][3], podcasts [11,42], and software use licenses [43]-in this study, the participants indicated using them very little, as compared to the presentation tools such as PowerPoint, Genially or Prezi, which the professors indicated using them very often. All of this could be due to the scarce digital training possessed by the professors, as indicated by them.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is significant that while some research studies report on the great use of digital tools [11]-mainly Augmented Reality [4,19,20], gamification [1][2][3], podcasts [11,42], and software use licenses [43]-in this study, the participants indicated using them very little, as compared to the presentation tools such as PowerPoint, Genially or Prezi, which the professors indicated using them very often. All of this could be due to the scarce digital training possessed by the professors, as indicated by them.…”
Section: Discussionmentioning
confidence: 76%
“…The appearance of the Information and Communication Technologies (ICT) in the education sphere has brought with it changes that have affected the two main actors of the education process, students and educators. In the case of the former, their social reality has invaded their academic one through the introduction of digital resources such as videogames [1][2][3], Augmented and Virtual Reality [4,5], Applications (Apps) that they already used in their everyday life [6,7], the new virtual learning environments supported by tele-training platforms [8], etc., to their learning process. Today's university students are catalogued as "millennials", students who were born in the digital era, and as a result, their link with technological resources is greater than in previous eras, where the students had a more analogical profile.…”
Section: Introductionmentioning
confidence: 99%
“…Despite different opinions, research continues to be conducted to better understand the relationship between video game usage and the social-emotional development process. Video games can have positive impacts on individuals' social-emotional development [9][10][11]. For instance, it has been found that video games can foster the development of social skills, such as cooperation and communication, especially in online multiplayer games where players must work together to achieve common objectives [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…La omnipresencia de las tecnologías digitales en el contexto sociocultural, así como el movimiento natural de los juegos y estos, a su vez, conllevan a la difusión generalizada de los juegos digitales y la gamificación en las práticas cotidianas, en las cuales, también se desarrollan procesos de ejercitación física y emocional (Conde y Rodríguez-Hoyos, 2017;Galindo-Domínguez, 2019;Guerra et al, 2018;Sánchez, 2018;Scolari, 2016).…”
Section: Introductionunclassified
“…La aplicación del método de elementos de juegos digitales en actividades gamificadas son iniciativas necesarias y cruciales para ayudar y actualizar prácticas pedagógicas al contexto sociocultural de la cibercultura (Guerra et al, 2018;Scolari et al, 2018;Torres et al, 2019).…”
Section: Introductionunclassified